2016
DOI: 10.1523/jneurosci.0935-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Nogo Receptor 1 Confines a Disinhibitory Microcircuit to the Critical Period in Visual Cortex

Abstract: A characteristic of the developing mammalian visual system is a brief interval of plasticity, termed the "critical period," when the circuitry of primary visual cortex is most sensitive to perturbation of visual experience. Depriving one eye of vision (monocular deprivation [MD]) during the critical period alters ocular dominance (OD) by shifting the responsiveness of neurons in visual cortex to favor the nondeprived eye. A disinhibitory microcircuit involving parvalbumin-expressing (PV) interneurons initiates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Thalamic axons themselves display plasticity after monocular deprivation, raising the question of specific contributions of cortical PV + interneurons to critical period plasticity (Jaepel et al, 2017;Sommeijer et al, 2017). Our study demonstrates that excitatory, thalamocortical (TC) inputs to PV + interneurons in V1 are essential for critical period closure, in agreement with a central role of cortical inhibition in critical period regulation (Gu et al, 2013;Kuhlman et al, 2013;Stephany et al, 2016;Sun et al, 2016). The identification of SynCAM 1 as a novel, PV + -autonomous molecular brake on plasticity highlights that distinct mechanisms control critical period opening vs critical period closure, and sheds light on the profound impacts of excitatory/inhibitor y imbalance and regulatory feedback loops that are frequently implicated in neurodevelopme nta l disorders (Ebert and Greenberg, 2013;Mullins et al, 2016;Nelson and Valakh, 2015;Zoghbi and Bear, 2012).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Thalamic axons themselves display plasticity after monocular deprivation, raising the question of specific contributions of cortical PV + interneurons to critical period plasticity (Jaepel et al, 2017;Sommeijer et al, 2017). Our study demonstrates that excitatory, thalamocortical (TC) inputs to PV + interneurons in V1 are essential for critical period closure, in agreement with a central role of cortical inhibition in critical period regulation (Gu et al, 2013;Kuhlman et al, 2013;Stephany et al, 2016;Sun et al, 2016). The identification of SynCAM 1 as a novel, PV + -autonomous molecular brake on plasticity highlights that distinct mechanisms control critical period opening vs critical period closure, and sheds light on the profound impacts of excitatory/inhibitor y imbalance and regulatory feedback loops that are frequently implicated in neurodevelopme nta l disorders (Ebert and Greenberg, 2013;Mullins et al, 2016;Nelson and Valakh, 2015;Zoghbi and Bear, 2012).…”
Section: Discussionsupporting
confidence: 71%
“…Other mechanisms that control excitatory drive onto PV + interneurons include Neuregulin-1/ErbB4 signaling (Fazzari et al, 2010;Sun et al, 2016), pentraxins (Chang et al, 2010;Gu et al, 2013;Pelkey et al, 2016) and the NogoR receptor (Stephany et al, 2016). Interestingly, all three are critical for ocular dominance plasticity (ODP), suggesting a pivotal role of excitatory drive onto PV + interneurons in the initiation of ODP (Gu et al, 2013;Kuhlman et al, 2013;McGee et al, 2005;Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3h-j ). Among the up-regulated genes, Rtn4r was reported to mediate intralaminar synaptic connectivity of visual cortical interneurons or a subclass of PV + interneurons 18,19 , which markedly sharpened grating orientation tuning and enhanced direction selectivity of nearby neurons 5 . Additionally, Nptxr has been hypothesized to be involved in activity-dependent synaptic plasticity 20,21 , as well as synaptic maturation through PV + interneurons in V1 22 .…”
Section: Singe-cell Rna Sequencing Of Somatic Aspiratesmentioning
confidence: 99%
“…This initial and transient reduction of PV cell activity establishes the conditions necessary for the experience‐dependent excitatory cortical plasticity for ocular dominance. Previous studies identified neurotrophins, extracellular matrix components, and synapse formation molecules as modulators of visual cortical plasticity (Berardi, Pizzorusso, Ratto, & Maffei, ; Gu et al, ; Huang et al, ; Murase, Lantz, & Quinlan, ; Pizzorusso et al, ; Stephany, Ikrar, Nguyen, Xu, & McGee, ; Sugiyama et al, ; Tropea et al, ). However, they do not account for the translation of brief sensory deprivation into functional changes in circuit connections.…”
Section: Introductionmentioning
confidence: 98%